Post-translational modifications of hormone-responsive transcription factors: the next level of regulation - Hill, Kristine (Journal of experimental botany, 2015)
Plants exhibit a high level of developmental plasticity and growth is responsive to multiple developmental and environmental cues. Hormones are small endogenous signalling molecules which are fundamental to this phenotypic plasticity. Post-translational modifications of proteins are a central feature of the signal transduction pathways that regulate gene transcription in response to hormones. Modifications that affect the function of transcriptional regulators may also serve as a mechanism to incorporate multiple signals, mediate cross-talk, and modulate specific responses. This review discusses recent research that suggests hormone-responsive transcription factors are subject to multiple modifications which imply an additional level of regulation conferred by enzymes that mediate specific modifications, such as phosphorylation, ubiquitination, SUMOylation, and S-nitrosylation. These modifications can affect protein stability, sub-cellular localization, interactions with co-repressors and activators, and DNA binding. The focus here is on direct cross-talk involving transcription factors downstream of auxin, brassinosteroid, and gibberellin signalling. However, many of the concepts discussed are more broadly relevant to questions of how plants can modify their growth by regulating subsets of genes in response to multiple cues.